Democracy through technocracy? Reinventing civil society as a state-monitored and unpaid service provider in the EU FLEGT VPA in Laos - Ramcilovic-Suominen, Sabaheta (Elsevier, 2024)
This paper analyses the European Union’s (EU’s) democratising agenda within the frame of the EU’s Forest Law Enforcement, Governance and Trade (FLEGT) Voluntary Partnership Agreement (VPA) in Laos. In particular, it focuses on the requirement for the participation of civil society organisations (CSOs) in the VPA and the Lao state actors’ responses to this requirement. I frame the VPA’s democratising agenda and its conditionality of civil society participation as acts of governmentality exercised by the EU in Laos. This EU governmentality is exercised through the EU and EU member states’ funded development partner in the frame of their project supporting the FLEGT VPA process in Laos. The Lao government responses and strategies to the EU governmentality resulted on the one hand in the Lao state’s governmentality towards domestic CSOs, and in counter-conduct (i.e. a subtle and sly resistance to some aspects of the VPA) on the other. First, by tracing the establishment of the Lao FLEGT Civil Society Organisations Network (FLEGT CSO Network), I highlight the trend of depoliticisation and rendering technical, where the EU-funded development partner, with full support and backing from the Lao state, trained the CSOs in various VPA and timber legality issues. In the training, the CSOs were given specific roles and tasks, building up their fields of expertise, and were integrated in the formal VPA organisational structures, which allowed for their scrutiny and tight survelience by the state. Second, I analyse the counter-conduct by the Lao government against a civil society that is independent from the state, which the government manifested through further disempowerment of CSOs and tightening of the CSO regulation shortly after the FLEGT CSO Network was established, while at the same time simulating democratisation by welcoming CSOs’ participation in the VPA. Summoning CSOs as compliant actors and unpaid service providers working for and alongside the state was in part enabled by the VPA’s own rendering technical approach. Hence, the EU’s VPA governmentality and the Lao state counter-conduct mutually reinforced one another, even if their initial agendas around democratisation and CSO engagement in forest governance and the VPA diverged.
Keywords: Civil society; Neoliberal governmentality; Rendering technical; Counter-conduct; EU external relations; FLEGT VPA; Laos